2020
DOI: 10.3390/cells9092143
|View full text |Cite
|
Sign up to set email alerts
|

miR-9-Mediated Inhibition of EFEMP1 Contributes to the Acquisition of Pro-Tumoral Properties in Normal Fibroblasts

Abstract: Tumor growth and invasion occurs through a dynamic interaction between cancer and stromal cells, which support an aggressive niche. MicroRNAs are thought to act as tumor messengers to “corrupt” stromal cells. We previously demonstrated that miR-9, a known metastamiR, is released by triple negative breast cancer (TNBC) cells to enhance the transition of normal fibroblasts (NFs) into cancer-associated fibroblast (CAF)-like cells. EGF containing fibulin extracellular matrix protein 1 (EFEMP1), which encodes for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 48 publications
0
12
0
Order By: Relevance
“…In most cases, miRNAs are regarded to be regulators of gene expression. 28 MiR-4732-5p could directly target the 3'UTR of tetraspanin 13 (TSPAN13) and suppress TSPAN13 expression at the mRNA and protein levels. 29 MiR-4732-5p has been demonstrated to function as a tumor suppressor in lung squamous cell carcinoma (LUSC).…”
Section: Discussionmentioning
confidence: 99%
“…In most cases, miRNAs are regarded to be regulators of gene expression. 28 MiR-4732-5p could directly target the 3'UTR of tetraspanin 13 (TSPAN13) and suppress TSPAN13 expression at the mRNA and protein levels. 29 MiR-4732-5p has been demonstrated to function as a tumor suppressor in lung squamous cell carcinoma (LUSC).…”
Section: Discussionmentioning
confidence: 99%
“…Exosomal or vesicular transfer between tumor cells and CAF secretome frequently results in an active feed-forward loop involving CAFs and tumor cells that increases tumor-promoting CAF activation and aggressive features in cancer cells. Specifically, Cosentino et al (2020) discovered that miR-9-mediated inhibition of EFEMP1 contributed to the upregulation of pro-tumor CAF phenotypes.…”
Section: Role Of Cafs In Therapy Resistancementioning
confidence: 99%
“…Further study from the same group also showed that miR-9 directly targets the ECM glycoprotein fibulin-3 (EFEMP1) in CAFs and EFEMP1 down-regulation is responsible for the observed increased CAFs motility upon miR-9 induction. Moreover, the supernatant of EFEMP1-depleted CAFs is able to confer resistance to cisplatin to TNBC cells, highlighting a two-way paracrine communication between these two cell types [ 36 ].…”
Section: Functional Impact Of Secreted Ncrnas On Surrounding Stromal Cells and At Metastatic Sites In Tnbcmentioning
confidence: 99%